Contrast Harmonic Endoscopic Ultrasound in Pancreatic Diseases - Rafael Mejuto-Fernandez; Julio Iglesias-Garcia (Korean Society of Gastrointestinal Endoscopy, 2021)
Endoscopic ultrasound (EUS) was first described in 1986, with the aim of overcoming the problems affecting transabdominal ultrasound imaging, mainly problems related to the interposition of gas, and artifacts produced by bone or fat. Now, EUS can be considered as the best method for the analysis of pancreatic diseases, overtaking the diagnostic accuracy of computed tomography and magnetic resonance imaging. However, fundamental B-mode imaging is limited for the diagnosis of solid pancreatic lesions, because most of them are depicted as heterogeneous and hypo-echoic, and it is difficult to differentiate between benign and malignant lesions. Similar to how perfusion patterns obtained by computed tomography or magnetic resonance imaging after injection of contrast agents allow for the characterization of focal lesions, EUS has also recently been introduced to the use of contrast agents for performing contrast-enhanced harmonic EUS (CEH-EUS), which has the capability to distinguish the type of perfusion between lesions and surrounding tissue. CEH-EUS has shown its usefulness for the diagnosis and characterization of solid pancreatic lesions. Moreover, CEH-EUS is also highly accurate for distinguishing non-neoplastic from neoplastic cysts in pancreatic lesions. Another potential role of CEH-EUS is its ability to direct EUS-guided tissue acquisition.